Recreation and its Health Benefits: A Critical Review - Ibhafidon, Akhere; Oforka, Okechukwu K.; Onuzulike, Nonye M.; Nwaobiala, Chinenye J. (International Journal of Human Kinetics, Health and Education, 2022)
Recreation which does not have a universal definition but has been described by various researchers is an important part of life. It has various benefits including being useful to health and wellbeing. This paper reviewed the health benefits of recreation. The paper focused on describing the concept of recreation. Recreational activities were defined, and the various health benefits including physical health benefits, mental health and social health benefits were discussed. The paper concluded among others that recreation though may not be appreciated by a lot of people helps one cope with the stress of daily activities. It also recommended among others that government should encourage and create awareness on the usefulness of recreation to health and national development.